KCNB1 gene polymorphisms and related indel as predictor biomarkers of treatment response for colorectal cancer – toward a personalized medicine. Issue 6 (June 2020) - Barbirou, Mouadh; Sghaier, Ikram; Bedoui, Sinda; Ben Abderrazek, Rahma; Kraiem, Hazar; Farah, Azer; Hassiki, Rym; Mokrani, Amina; Mezlini, Amel; Almawi, Wassim Y; Loueslati-Yacoubi, Besma; Bouhaouala-Zahar, Balkiss
The KCNB1 gene variants were differentially associated with cancers. However, their association with colorectal cancer has not yet been explored. We investigated the contribution of the KCNB1 gene variants rs3331, rs1051295, and indel (insertion/deletion) rs11468831 Polymorphism as predictors of the treatment response in colorectal cancer patients. A retrospective study, which involved 291 Tunisian colorectal cancer patients (aged 60.0 ± 13.1 years), who were stratified into responder and non-responder groups, according to TNM stages and their responsiveness to chemotherapy based on fluorouracil. KCNB1 genotyping was performed with amplification-refractory mutation system–polymerase chain reaction, and was confirmed by Sanger sequencing. Sex-specific response was found and colorectal cancer females are less likely to achieve a positive response during the chemotherapy strategy, compared to males. Weight and body mass index, tumor size, and tumor localization are considered as predictive factors to treatment responsiveness. Carriage of rs11468831 Ins allele was significantly associated with successful therapy achievement ( p adjusted  < 0.001). Stratification of colorectal cancer patients' response according to tumor localization and TNM stages reveals negative association of rs3331 Major allele to treatment response among the patients with advanced cancer stages (subgroup G2). The presence of rs3331 (homozygous minor) C/C genotype was positively associated with decline in carcino-embryonic antigen ( p  = 0.043) and CA19-9 ( p  = 0.014) serum levels. On the other hand, the presence of rs1051295 (homozygous minor) A/A genotype was correlated with marked decline in CA19-9 serum levels. KCNB1 haplotype did not reveal any association between haplotypes and treatment response. The results obtained suggest that gender-specific strategies for screening treatment and prevention protocols as well as KCNB1 variants may constitute an effective model for ongoing personalization medicine.